Preoperative predictors of lateral neck lymph node metastasis in papillary thyroid microcarcinoma - Liu, Zheng (Medicine (Baltimore), 2017)
Lateral lymph node metastasis (LNM) is not uncommon in papillary thyroid microcarcinoma (PTMC). Our present study aimed to investigate the risk factors associated with lateral LNM in PTMC. We retrospectively collected data pertaining to 366 patients with PTMC who underwent surgery at our center from 2010 to 2015. These patients were divided into the following 2 groups: a lateral LNM-positive group and a lateral LNM-negative group. Clinical and ultrasound data were compared between the 2 groups to determine the risk factors associated with lateral LNM. Univariate and multivariate analyses indicated that capsule invasion (OR = 3.995, 95% CI, 2.148–7.430) and upper portion location (OR = 4.541, 95% CI, 2.444–8.438) were significant risk factors for lateral LNM of PTMC and that capsule invasion (AUC = 0.666) and upper portion location (AUC = 0.678) could be used to predict lateral LNM of PTMC. Moreover, the patients in lateral LNM positive group exhibited significantly higher rates of tumor recurrence or metastasis than the patients in lateral LNM negative group (P = 0.027). Patients with PTMC located in the upper portion or exhibiting capsule invasion should receive meticulous preoperative evaluations for lateral LNM, prophylactic lateral LND may be considered.